EVALUATING TREATMENT-SEEKING BEHAVIOR AND THE RELATED FACTORS AMONG THE DWELLERS OF SAFASHAHR CITY - Rashidi, Sareh; Yazdanpanah, Abbas; Ghayiibarzabad, Parviza (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study aims to recognize and evaluate treatment-seeking behavior and the related factors among the dwellers of Safashahr city. Methods: The current applied research is cross-sectional with a population size of 380 and executed in a systematic random sampling among the dwellers of Safashahr city and the villages governed by it. SPSS version 22 has been utilized for analyzing the data in this study. T-test, Chi-square variance analysis, Pearson test, and Spearman test have been used to evaluate the significance and the relationship between the understudy variables with the treatment-seeking variables. Results: 75% of participants in the study have reported being diagnosed with illness in the past 6 months. Visiting family physician was ranked highest with an average 3.36 followed by public hospitals with an average of 3.05. However, they chose to go to clinic centers with an average of 2.1. Self-medication has been reported for an average of 2.6% and 88.2% of the participants in this study have preferred to ignore the medium and less than medium treatment. In this study, a significant relationship has been found between age, number of family members, living location, salary, habitation status, and type of insurance with at least one of the search-for-treatment (p<0.05). Conclusion: Taking into account the findings of the research, lifting the society's awareness about the consequences of self-medication and ignorance toward treatment, continuing and executing the urban family physician in other areas, implementation of measures for limiting access to unprescribed medications, increasing satisfaction, and trust toward public sector and provision and allocation of health resources across cities are recommended as appropriate solutions to improving the pattern of using health services. Keywords: Treatment seeking behavior, Self-medication. Objective:Thepresentstudyaimstorecognizeandevaluatetreatment-seekingbehaviorandtherelatedfactorsamongthedwellersofSafashahrcity. Methods:Thecurrentappliedresearchiscross-sectionalwithapopulationsizeof380andexecutedinasystematicrandomsamplingamongthe dwellersofSafashahrcityandthevillagesgovernedbyit.SPSSversion22hasbeenutilizedforanalyzingthedatainthisstudy.T-test,Chi-square varianceanalysis, Pearsontest,andSpearmantesthavebeenusedtoevaluatethesignificanceandtherelationshipbetweentheunderstudy variables with the treatment-seeking variables. Results:75%ofparticipantsinthestudyhavereportedbeingdiagnosedwithillnessinthepast6months.Visitingfamilyphysicianwasranked highestwithanaverage3.36followedbypublichospitalswithanaverageof3.05.However,theychosetogotocliniccenterswithanaverageof 2.1.Self-medicationhasbeenreportedforanaverageof2.6%and88.2%oftheparticipantsinthisstudyhavepreferredtoignorethemediumand lessthanmediumtreatment.Inthisstudy,asignificantrelationshiphasbeenfoundbetweenage,numberoffamilymembers,livinglocation,salary, habitation status, and type of insurance with at least one of the search-for-treatment (p<0.05). Conclusion:<span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; letter-spacing: -.6pt;" lang="EN-US">Takingintoaccountthefindingsoftheresearch,liftingthesociety'sawarenessabouttheconsequencesofself-medicationandignorance towardtreatment,continuingandexecutingtheurbanfamilyphysicianinotherareas,implementationofmeasuresforlimitingaccesstounprescribed medications,increasingsatisfaction,andtrusttowardpublicsectorandprovisionandallocationofhealthresourcesacrosscitiesarerecommendedas appropriate solutions to improving the pattern of using health services. Keywords: Treatment seeking behavior, Self-medication.